Persuasive Language Analysis in Mie Gacoan's Instagram Post in February 2024 - Habibatul Ummah; Fazaraul Farahiyyah Ad (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2024)
This research addresses the use of persuasive language in Instagram posts of Mie Gacoan's account during February 2024, with a pragmatic approach to understanding the meaning hidden behind speech. The persuasive language used is designed to attract the audience's attention through a relaxed style, humor, and relevance to everyday life. With a pragmatic approach, this research analyzes the relationship between form, meaning and context in the language used. In Mie Gacoan's Instagram Account post, persuasive language is used to build emotional connections with the audience, effectively convey promotional messages, and create engaging communication experiences. Through descriptive qualitative methods, the study identified and grouped data by specific categories, resulting in a deep understanding of the persuasive strategies applied. The results show that the use of persuasive language combined with a pragmatic approach can increase the attractiveness of posts, as well as be effective in influencing the audience to take the desired action.